Political Behavior Of Muslim Voters In Giving Vote Of Political Support - Mohammad Syawaludin (CV. Syntax Corporation Indonesia, 2022)
This study determines political choices in the legislative general election in Palembang by responding to political realities that are not directly related to religious issues and the creation of voter polarization and voter subjectivity. Political relations between religion and other political instruments are considered something that does not show their identity. In this study, the researcher used a qualitative method with a phenomenological study and a political sociology approach. Followed by content and interpretive analysis, the results of this study found that Muslim citizens have three attitudes, namely; first; positive toward legislative candidates. This means that Muslims know, believe, agree with themselves as voters and vote based on the vision and mission of the legislative candidates. Both neutral attitudes know themselves as voters who care enough about the vision and mission of the legislative candidates. The third negative attitude is when the Muslim community does not know, does not believe, does not agree, and is apathetic.